The validity of rheumatoid arthritis diagnoses in Finnish biobanks - Paltta, J; Heikkilä, HK; Pirilä, L; Eklund, KK; Huhtakangas, J; Isomäki, P; Kaipiainen-Seppänen, O; Kristiansson, K; Havulinna, AS; Sokka-Isler, T; Palomäki, A; FinnGen investigators (TAYLOR & FRANCIS LTD, 2022)
Objective: The aim of this study was to determine the validity of rheumatoid arthritis (RA) diagnoses in patients participating in Finnish biobanks.
Method: We reviewed the electronic medical records of 500 Finnish biobank participants: 125 patients with at least one visit with a diagnosis of seropositive RA, 125 patients with at least one visit with a diagnosis of seronegative RA, and 250 age- and gender-matched controls. The patients were chosen from five different biobank hospitals in Finland. A rheumatologist reviewed the medical records to assess whether each patients' diagnosis was correct. The diagnosis was compared with the diagnostic codes in the Finnish Care Register for Health Care (CRHC) and special reimbursement data of the Social Insurance Institution of Finland.
Results: The positive predictive value (PPV) of CRHC diagnosis of RA (for seropositive and seronegative RA combined) was 0.82. For patients with a special reimbursement for anti-rheumatic medications for RA, the PPV was 0.89. The PPV was higher in patients with more than one visit. For one, two, five, and 10 visits, the PPV was 0.82, 0.85, 0.89, and 0.90, respectively, and for patients who also had the special reimbursement, the PPV was 0.89, 0.91, 0.93, and 0.94 for one, two, five, and 10 visits, respectively. In patients positive for anti-citrullinated protein antibodies, the PPV was 0.98.
Conclusion: These results demonstrate that the validity of RA diagnoses in Finnish biobanks was good and can be further improved by including data on special reimbursement for medication, number of visits, and serological data.